Metodologia para aferição da competitividade de sistemas de cria na bovinocultura de corte - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The beef cattle presents a broad socio-economic relevance, both external and internal market, but has major obstacles to be diagnosed and corrected. In recent decades the Brazilian economy has numerous transformations, that made the productive and economic efficiency became primary caracteristics to establish in a meat market increasingly competitive and globalized. This research aims to generate a method to assess the internal competitives of creating production systems in beef cattle, with respect to technological, managerial, marketing relations and institutional environment. For this, steps were defined for the implementation of this research: literature review related to the theme competitiveness and inserted efficiency in the context of the production chain of beef; definition of research focus (cattle of create); formatting and subsequent validation of the method from the application of on-site surveys in production systems and the subsequent measurement of the internal competitiveness of production systems through drivers, factors and sub-factors by mathematical equations. The competitive index creates system will have an amplitude of zero (0) to ten (10) as follows: 0-2.0 (no competitive); 2.1 to 4.0 (uncompetitive); 4.1 to 6.0 (neutral); 6.1 to 8.0 (competitive) and 8.1 to 10.0 (very competitive). The method was effective for the initial diagnostic of rural enterprises working with creates the beef cattle systems, demonstrating to be aligned with strategic planning of rural properties. The methodology allows farmers to know the main strengths and weaknesses of your internal environment, enabling the correct decision-making. Finally the method is easy to apply and can be used in the various regions where beef cattle is developed and can be an important sector diagnostic tool activity through the identification of barriers to the development of the productive chain, especially "inside gate" .
Methodology for measuring the competitiveness creates systems in beef cattle
Keywords: Pecuária; Relações de mercado; Criação de gado; Bovinos de corte; Competitividade; Livestock; Management; Beef cattle; Market relations; CNPQ::CIENCIAS AGRARIAS